Effect of licorice extract (Glycyrrhiza glabra) on some semen traits for local black turkey males - AL-Janabi, Yihea Abas Merdas; Al-janabi, Thamer Kareem; Altaie, Salam Merza Suhail (Journal of Kerbala for Agricultural Sciences, 2020)
This study was conducted at the poultry farm for department of Allatefya Researches, Agricultural and biological researches directorate, ministry of sciences and technology, during the period from 20/8/2019 to 28/12/2019. The aim of this study was to investigate the effect of licorice ( Glycyrrhiza glabra) extract on some semen traits for local black turkey males. A total of 36 local Iraqi turkey males in 44 weeks old were used in this study. The turkey males were randomly distributed on 4 treatments, each treatments consisted of 9 birds depends on level of licorice addition. Birds were fed during the experimental period on diet contain 2950 Kcal metabolic energy / kg and 18 % crude protein/ kg. Licorice extract was added with drinking water for three levels 5g, 10g, and 15g to treatments T2, T3 and T4 respectively. While T1 treatment stay without any addition as control group. The birds were housed in ground pens (cages) during this study. Semen was collected after ganders trained for two weeks to give semen before the collection began, the semen collection by using abdominal massage procedure. The characteristics were investigated were ejaculate volume, individual motility, mass motility, sperm concentrations, percentage of dead spermatozoa, deformation spermatozoa ratio and spermatocrit. Results revealed that T4 (15 g per liter) recorded highest values in all traits except in deformation spermatozoa ratio as compared with other treatments (T1, T2 and T3) in most of all experimental period. On the other hand T3 (10 g per liter) achieved high significant effect compared with T2 (5 g per liter) and T1 (0 g per liter), whereas T1 recorded lowest values during all experimental period. However, the overall means of all traits achieved the same trend of treatments effect. While deformation spermatozoa ratio trait had not significant affects recorded from licorice extract addition on this study.